"It's Simply Because We're Black Men": Black Men's Experiences and Responses to the Killing of Black Men. Issue 2 (June 2016) - Brooms, Derrick R.; Perry, Armon R.
Given the recent attention to high-profile cases of unarmed Black men being killed by law enforcement officials and the subsequent #BlackLivesMatter movement, additional work is needed to more fully understand how African American men make meaning of their own personal realities and how they connect with and within the larger narrative of Black life in the United States. To contribute to this literature, the current study analyzes qualitative interview data from 25 Black men focused on their self-conceptions of race, stereotyping, and profiling. The findings reveal the men's perceptions and experiences with racism and stereotyping, the strategies that they employ in response to being stereotyped and profiled, and their reflections on the recent killings of Black men. This research provides an opportunity to investigate how Blackmaleness—the combined impact of their racialized and gendered identities—connects and operates in the lives of Black men.